INTRASPECIFIC VARIATION IN WING SHAPE OF DOLICHOPUS PLUMIPES (DIPTERA, DOLICHOPODIDAE) (Acta Entomologica Serbica, 2017)
A study of 128 specimens of Dolichopus plumipes from 9 geographical regions was conducted to evaluate the interpopulation variation in wing shape. The wing shape was described by 7 morphometric characters. The shape variation was examined using principal component analysis and t-test. The wing length and related characters were found to differ in shape between the western, eastern, northern and southern specimens. Correlation and regression analysis showed that geographic variation in wing length was strongly associated with longitude; and a significant linear component was revealed.